Kriptanalisis Algoritma Vigenere Chiper dengan Algoritma Genetika untuk Penentuan Kata Kunci - Tsuraya Ats Tsauri; Nurochman Nurochman (UIN Sunan Kalijaga Yogyakarta, 2017)
Cryptanalysis is the art to solve without key ciphers, in contrast to cryptography, namely to maintain the confidentiality of data by encode a plaintext. Vigenere ciphers is one of the kriptanalisis algorithm. Brute force attack and exhaustive attack is a technique of kriptanalisis vigenere ciphers, but less optimal in result. In my research this time proposed a way of solving the secret key (Cryptanalysis), using a genetic algorithm on text Indonesia-speaking ciphers. .The first step in this study performed a chromosome design would be the length of the keyword, the method used is the coincidence index (IOC), the IOC values with text Indonesian is 0,075. To get the value of fitness done the search weights by comparison Word decryption of keywords with Indonesian Language Dictionary. Genetic algorithms will seek all possible keywords, there are genetic algorithms in the process of reproduction includes crossover, mutation and elitisme. There are parameters that are included in the process of a keyword search that is the value of the probability of crossover, mutation probability and population, number of the parameter that you want to optimize to get keywordsThis analysis is performed on the five scenarios with any combination of parameters, number of characters chipertext and two types of different keywords. After 1000 times testing with a combination of parameters generated 467 the data successfully guessing keywords within approximately 60 minutes. With the testing of two different keywords and two different ciphers text amount done by as much as five times the test showed that both have the value of the average test time the fastest standard deviation value. After an analysis of the results of the research, the optimal parameters is obtained with a value Pc 0.09, Pm 0.3 and Pop_size 20.Keywords : Cryptanalysis, Genetic Algorithm, Vigenere Chiper, Index Coincidence.